Influence of Cobalt (II) Chloride Catalysed on the Thermal and Optical Characterization of PEO Based Solid Polymer Electrolytes - Chapi, Sharanappa; Devendrappa, H. (Journal of Research Updates in Polymer Science, 2015)
Solution-casting technique was employed for the preparation of solid polymer electrolyte based polyethylene oxide (PEO) with 0, 1, 3 and 5 weight percentage cobalt chloride (CoCl2) films were characterized by X-ray Diffractometry (XRD), Differrential Scanning Calorimetry (DSC), Scanning Electron Microscope (SEM) and Ultra Violet-Visible (UV-Vis.) Spectroscopy methods. The optical band gaps, absorption band edges and Urbach energy shows decrease with increasing of Co+2 ion concentration in the polymer matrix because of the formation of free radicals or cluster. The Thermogravimetry (TG) and Derivative Thermogravimetry (DTG) were used to examine the thermal stability of the film and it was found that the stability of the complexes is higher than that of the pure PEO due to the addition of CoCl2. The wavelength position of a fluorescence emission band varied by increasing of a dopant wt % of salt.